Juntas generales de accionistas no presenciales - Leturia López, Eduardo Félix (2024)
This paper seeks to analyze the circumstances experienced by the vast majority of corporations to be able to call and hold General Shareholders’ Meetings since the establishment of the State of National Emergency, on March 16, 2020, which restricted the rights related to freedom of movement and of meeting, in those in which their statutes did not regulate that the General Meetings of Shareholders can be held remotely and nor did the General Corporation Law provide an adequate response to such an unusual circumstance. Likewise, it shows the legislative solutions that were issued, starting with the companies under the jurisdiction of the Securities Market Superintendence, then the cooperatives and finally the other kind of corporations and legal entities.